2022
DOI: 10.1177/03635465221096490
|View full text |Cite
|
Sign up to set email alerts
|

Loading Mesenchymal Stem Cell–Derived Exosomes Into a Traditionally Designed Rotator Cuff Patch: A Potential Strategy to Enhance the Repair of Chronic Rotator Cuff Tear Associated With Degenerative Changes

Abstract: Background: Retraction and degenerative changes of chronic rotator cuff tears limit the healing capacity after routine surgical repair. Purpose: To fabricate a mesenchymal stem cell–derived exosome (MSC–Exos) loaded patch and evaluate the effect of this patch on the activity of rabbit tenocytes in vitro and on the repair of chronic rotator cuff tears associated with degenerative changes in vivo. Study Design: Controlled laboratory study. Methods: The MSC–Exos loaded patch was fabricated using a dynamic wet-spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 42 publications
0
40
0
Order By: Relevance
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After searching the six databases, a total of 1794 studies were found. Forty-five articles were included after screening and all of them were case–control studies [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 ]. Another article was included by searching the references of the included articles and review articles related to the topic [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…All studies had a low risk of baseline characteristics under selection bias, random outcome assessment under detection bias, attrition bias, reporting bias, and other biases [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. All studies reported baseline characteristics of the animals used which included the species, age and gender of the animals, and the outcomes were randomly assessed [ 8 , 9 , 47 , 48 , 49 , 50 , 51 , 52 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MSC‐Exos loaded patch was found to enhance the repair of chronic rotator cuff tears by providing mechanical support and mitigating muscular degeneration. [ 82 ] Similar therapeutic strategies were also developed from adipose‐derived stem cells. [ 83–85 ] A novel cell‐free treatment approach using exosomes isolated from human adipose‐derived stem cells (ASCs‐Exos) has shown promise in preventing muscle atrophy and improving biomechanical properties in a rat model of a massive rotator cuff tear.…”
Section: Introductionmentioning
confidence: 99%